In situ observational data of particulate organic carbon off western Patagonia in Jan/Feb 2017 - Andrea Corredor-Acosta; Jose Luis Iriarte (PANGAEA, 2023)
The dataset compiles in situ observational data obtained during the R/V Mirai MR16-09 cruise (2017-01-21 to 2017-02-03) off western Patagonia, Chile. Seawater samples for particulate organic carbon (POC) concentration (one replica) were collected from 0, 25, and 200 m in 1-4.5 L polycarbonate bottles. The samples for POC concentration were filtered immediately onto pre-combusted (450°C for 6h) GF/F filters (Whatman, Kent, UK). Samples collected from surface and 25 m depth were incubated on-deck in an incubator cooling by recirculated sea surface water and samples from the aphotic zone were incubated in a thermostatic incubator under dark condition. The incubations were terminated by gentle vacuum filtration of the samples through a pre-combusted GF/F filter after 24 h. The filters were kept frozen before laboratory analysis. The filters were dried at 50°C overnight, and then exposed to hydrogen chloride (HCl) fumes for 2 h. Total carbon was determined using a mass spectrometer (DELTA V advantage - Thermo Electron, Waltham, Massachusetts, USA) connected to an elemental analyzer (Flash EA - Thermo Electron).